Liberação de potássio e alteração mineralógica em argissolos subtropicais - Chaves, Estéfane (2014)
The potassium (K) of a given soil depends primarily on its parent material. The K in the soil can be conceptually divided into: structural K, non-exchangeable K, exchangeable K, and K in the solution. Studies have shown that organic acids, which occur in the rhizosphere of plants and soil microorganisms can facilitate the mineral weathering with the formation of organometallic complexes. The availability of K is an important factor of the productivity for crops and their dynamics in the soil is closely related to its mineralogy. Organic acids of low molecular weight have been used in kinetic studies to release K in soils. The purpose of this study was to (a) evaluate the dynamics of K release in the presence of oxalic acid (OA) in three subtropical Alisols, (b) consider the mineralogical changes caused by soil contact with the acid, and (c) to quantify reserve K existing in three size fractions (sand, silt and clay). Samples of three Alisols of Rio Grande do Sul (RS) were collected. The fractions were separated, and burning organic matter. Furthermore, we determined the levels of K in solution, available K, exchangeable K, non-exchangeable K and total K in each fraction and the fine earth fraction (TFSA). The fractions were subjected to the dynamics of K release test, X-ray analyzes being performed before and after these procedures. PBAC1 and PBAC2 had the highest K total reserve and also the greatest content released during the dynamic test than the PVD. In the XRD patterns were identified quartz and feldspar in the sand and silt fractions. The dominant clay smectite, illite, kaolinite, disordered kaolinite, quartz, microcline, albite and magnetite were identified. No significant differences were observed in mineralogy after contact with the OA. The PBAC1 and PBAC2 soils had the greatest capacity to supply the structural K. The clay fraction of the three soils was the fraction that contributed with provision of K, but the silt fraction of the PBAC2 also released large amount of K.